Neolithic foundations in the Karama valley, West Sulawesi, Indonesia. (26th August 2014) - Anggraeni,; Simanjuntak, Truman; Bellwood, Peter; Piper, Philip
Abstract : Excavations at three open-air sites in the Karama valley of West Sulawesi have revealed similar suites of ceramics and overlapping chronologies. The pottery from the basal layers at Minanga Sipakko and Kamassi resembles that of the Philippines and Taiwan, and suggests the settlement of migrants from those areas, consistent with the theory of Austronesian expansion. The absence of the flaked lithic technology typical of earlier Sulawesi populations indicates that these two sites do not represent the indigenous adoption of Neolithic features. The Karama valley evidence underlines the importance, in the quest for the earliest farmers, of research at open-air sites close to agriculturally suitable land, while indigenous populations may have continued for some time to occupy remote caves and rockshelters.